Trypanosoma cruzi Entrance through Systemic or Mucosal Infection Sites Differentially Modulates Regional Immune Response Following Acute Infection in Mice - de Meis, Juliana; de Albuquerque, Juliana B.; dos Santos, Danielle S.; Farias-de-Oliveira, Désio A.; Berbert, Luiz R.; Cotta-de-Almeida, Vinícius; Savino, Wilson (Frontiers in Immunology, 2013)
Acute Chagas disease is characterized by a systemic infection that leads to strong activation of the adaptive immune response. Outbreaks of oral contamination by the infective protozoan Trypanosoma cruzi are frequent in Brazil and other Latin American countries, and an increased severity of clinical manifestations and mortality is observed in infected patients. These findings have elicited questions about the specific responses triggered after T. cruzi entry via mucosal sites, possibly modulating local immune mechanisms and further impacting regional and systemic immunity. Here, we provide evidence for the existence of differential lymphoid organ responses in experimental models of acute T. cruzi infection.